Türk hukukunda eser sahibinin çoğaltma ve yayma hakları - Genç, Arzu (My University, 2002)
Tezimizin başlığı, Türk Hukukunda Eser Sahibinin Çoğaltma ve Yayma Haklarıdır. Tezimizde, çoğaltma ve yayma haklarının özellikleri, sınırları ve ihlali halleri Türk Hukuku ve uluslararası sözleşmelere göre incelenmiştir. Amacımız çoğaltma ve yayma haklarının ihlaline ilişkin önleyici tedbirleri ve ihlal gerçekleştiğinde eser sahibinin başvurabileceği dava haklarını belirlemektir. The title of the master is Owner's İntellectual Property Right To Publich And Distribute İn Turkish Law. The thesis analyses, among Intellectual Property Rights, the rights to print and distribute, their limits, and the violations of these righs in material Turkisch Law particularly in accordance with the Law for protecting İntellectnal and Artisanal Works and other regulation compared with international agreements and regulations. It is an objective of the study to outline the rights of the owner and the precautions to protect the owner from acts like infringements, illegal copying, printing and distribution.
Keywords: Hukuk